Shepherd on Hume’s Argument for the Possibility of Uncaused Existence - David Landy (Journal of Modern Philosophy)
Shepherd’s argument against Hume’s thesis that an object can begin its existence uncaused has received short shrift in the secondary literature. I argue that the key to understanding that argument’s success is understanding its dialectical context. Shepherd sees the dialectical situation as follows. Hume presents an argument against Locke and Clarke the conclusion of which is that an object can come into existence uncaused. An essential premise of that argument is Hume’s theory of mental representation. Hume’s theory of mental representation, however, is itself implausible and unsupported. Therefore, one need not accept this premise or this conclusion. Thus, Shepherd proceeds to her discussion of the relation of cause and effect free to help herself to the thesis that every beginning of existence must have a cause. Additionally, she elsewhere pays down the debt she incurs in that argument by presenting her own alternative theory of mental representation, which is both plausible in its own right, and can account for the error that she takes Hume to make.